Integrated control system simulation for supporting changes of routing strategy in an automated material flow system - Abdul Rahman, Azrul Azwan; Seliger, Günther (Elsevier B.V., 2013)
Increased demand for customised products, sophisticated scheduling requirements caused by shorter product life cycles and hardly foreseeable disturbances have created a new challenge for the manufacturing industry. Planned production schedules often become ineffective in actual execution on the shop floor. If forecasts become less and less accurate, support for continuous changes is helpful. Given the high degree of automation in manufacturing systems, automatic control systems have become central to shop floors’ responsiveness. However, their state-of-the-art architectures are unable to cope with the challenge successfully. Improvement in information and communication technology makes the integration of simulation and control system more promising. The paper proposes an approach for supporting changes of control strategy in an automated material flow system by utilising the integration. The approach includes (re-)planning of the automated material flow system, commissioning its logic control and controlling the material flow.